PARP inhibitors as maintenance therapy in newly diagnosed advanced ovarian cancer: a meta‐analysis. (2nd August 2020) - Lin, Q; Liu, W; Xu, S; Shang, H; Li, J; Guo, Y; Tong, J
Abstract : Background: Up to 70% of patients with advanced ovarian cancer have a relapse after primary therapy. New agents and approaches are urgently needed to avoid or slow down this recurrence. Objectives: To investigate the efficacy of PARP inhibitors (PARPis) as maintenance treatment in patients with newly diagnosed advanced ovarian cancer. Search strategy: PubMed, MEDLINE, EMBASE, Cochrane Library and Web of Science databases. Selection criteria: All randomised clinical trials (RCTs) that compared PARPis with placebo as first‐line maintenance therapy in ovarian cancer. Data collection and analysis: Two reviewers extracted data. Pooled hazard ratio (HR) and risk ratio (RR) with 95% confidence interval (CI) were calculated. Main results: PARPis were associated with significant improvement of progression‐free survival (PFS) in advanced epithelial ovarian cancer (AeOC) (HR = 0.53, 95% CI 0.40–0.71; P < 0.0001). The benefit was not only in women with BRCA mutations (HR = 0.35, 95% CI 0.29–0.42; P < 0.00001) and homologous recombination deficiency (HRD) (HR = 0.43, 95% CI 0.32–0.60; P < 0.00001), but also in those with nonmutated BRCA (HR = 0.72, 95% CI 0.63–0.82; P < 0.00001) and even non‐HRD (HR = 0.83, 95% CI 0.70–0.99; P = 0.04). Conclusions: PARP inhibitors are effective as maintenance therapy among patients with newly diagnosed advanced ovarian cancer after platinum‐based chemotherapy, regardless of BRCA mutation or HRD status. Tweetable abstract: PARPis provide a significant PFS benefit as first‐line maintenance therapy in patients with newly diagnosed advanced ovarian cancer. Tweetable abstract: PARPis provide a significant PFS benefit as first‐line maintenance therapy in patients with newly diagnosed advanced ovarian cancer.